Nanofluids In Battery Cooling System - Lee, Chern Khai (Universiti Sains Malaysia, 2018)
Thermal implications related to heat generation and potential temperature excursions during operation in lithium-ion batteries are of critical importance for electric vehicle safety, performance and life. Concurrently, appropriate thermal management strategies for lithium-ion batteries are crucial to maintain cell temperatures within a desired range. Hence, the development of nanofluids to improve heat transfer capabilities in car batteries have attracted intense research activities in recent years. Nanofluids, which are stably dispersed or suspended nanosized particles in heat transfer liquids have attracted substantial interest because they offer a promising alternative to the inherent problems of conventional working fluids. Besides, the nanoparticles do not settle in the fluid and do not cause clogging and damage to surfaces as with micron sized particles. The problem statement of the project is to analyze the efficiency of nanofluids as heat transfer fluids for active thermal management in car batteries. The research experimentally investigates the use of silica nanofluids and distilled water. In order to determine the efficiency of nanofluid as heat transfer fluids, experimental data such as Reynolds number, heat transfer coefficient and Nusselt number of water and water based silica nanofluid that flow through a circular tube (Di=0.8 mm) are obtained. The flow was assumed as fully laminar flow with uniform heat flux applied to the tube surface. Different weight concentrations of silica/water nanofluids (0.1, 0.2, 0.3, 0.4, 0.5wt %) were used in the experiment. Based on the data collected, graphs of heat transfer coefficient of nanofluids at different concentrations and distilled water versus axial distance over inner diameter of tube (Z/Di) and % heat transfer enhancement of nanofluis at different concentrations and distilled water versus (Z/Di) were plotted and analyzed. The results concluded that heat transfer coefficient and Nusselt number was significantly enhanced using silica nanofluids as compared to distilled water as heat transfer fluids. Higher values of heat transfer coefficient and Nusselt number indicate that more heat is being transferred from the tube to the fluid which results in a significant reduction of the overall tube surface temperature. The heat transfer enhancement was found to be dependent on the nanoparticle concentrations. The maximum enhancement was recorded for 0.4 wt. % silica nanofluids with 6.9% increase in heat transfer coefficient.